2015
DOI: 10.1002/ejic.201500010
|View full text |Cite
|
Sign up to set email alerts
|

PEPPSI‐Effect on Suzuki–Miyaura Reactions Using 4,5‐Dicyano‐1,3‐dimesitylimidazol‐2‐ylidene‐Palladium Complexes: A Comparison between trans‐Ligands

Abstract: The PEPPSI (Pyridine Enhanced Precatalyst Preparation, Stabilization and Initiation) complexes 12-15 with the structure [PdCl 2 {(CN) 2 IMes}(3-R-py)] (12: R = H; 13: R = Cl; 14: R = Br; 15: R = CN) bearing the maleonitrile-based N-heterocyclic carbene (NHC) (CN) 2 IMes ({(CN) 2 IMes}: 4,5-dicyano-1,3-dimesitylimidazol-2-ylidene) were prepared. Solid state structures of 14 and 15 were obtained. Complexes 14 and 15 adopt a slightly distorted square-planar coordination geometry in the solid state with the substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The presented catalysts have in our opinion advantages over the recently reported PEPPSI-type complexes which formed Pd(0) NPs operating according to the heterogeneous pathway [22].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The presented catalysts have in our opinion advantages over the recently reported PEPPSI-type complexes which formed Pd(0) NPs operating according to the heterogeneous pathway [22].…”
Section: Discussionmentioning
confidence: 97%
“…There are many examples of the application of PEPPSI complexes in the Suzuki-Miyaura reaction, in which their excellent catalytic activity and versatility are clearly evidenced [18][19][20][21][22][23][24]. In contrast, their applications in the Hiyama coupling are rather scarce [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Table shows a comparison between the efficiency of this catalytic system in Suzuki‐Miyaura coupling reaction of aryl chlorides and other catalytic systems. The results showed that the most active palladacycles, N‐heterocyclic carbenes (NHCs) and pyridine‐enhanced precatalyst preparation stabilization and initiation (PEPPSI)‐type Pd complexes need to be used in high loadings and showed lower activity with aryl chloride substrates . From an industrial view point, the low catalyst loading and short reaction time make this palladacycle as an ideal catalyst for the Suzuki‐Miyaura coupling reaction.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the reactivity of mercury with palladium in N-heterocyclic carbene (NHC) and in C,N-and C,P-palladacycle ligand systems has raised concerns about the accuracy of the test. 27−29 While many have used the inhibition of catalysis upon the addition of mercury prior to catalyst activation as evidence for the involvement of heterogeneous species, 30,31 Gorunova and co-authors suggested that this could indicate reactivity with the homogeneous precatalyst. 28 Work by Chernychev and coauthors recently provided evidence for such interactions, demonstrating how the precatalyst tris(dibenzylideneacetone)dipalladium(0), Pd 2 (dba) 3 , reacted with Hg 0 to form free dba and other organomercuric species, leading to the nearcomplete disappearance of dissolved palladium within 30 min.…”
Section: ■ Introductionmentioning
confidence: 99%